For God and kaiser the Imperial Austrian Army, 1619-1918 - Bassett, Richard (Yale University Press, 2015)
Among the finest examples of deeply researched and colorfully written military history, Richard Bassett's 'For God and Kaiser' is a major account of the Habsburg army told for the first time in English. Bassett shows how the Imperial Austrian Army, time and again, was a decisive factor in the story of Europe, the balance of international power, and the defense of Christendom. Moreover it was the first pan-European army made up of different nationalities and faiths, counting among its soldiers not only Christians but also Muslims and Jews. Bassett tours some of the most important campaigns and battles in modern European military history, from the seventeenth century through World War I.